PENGENALAN BUDAYA LOKAL MELALUI PERMAINAN TRADISIONAL DI SDN SUKOREJO: PENGENALAN BUDAYA LOKAL MELALUI PERMAINAN TRADISIONAL DI SDN SUKOREJO - Dewi, Anggra Lita Sandra; Rahmawati, Ery; Dewi, Galuh Kartika (Jurnal Edukasi Pengabdian Masyarakat, 2025)
Traditional games are a type of folk game activity that is the cultural heritage of the ancestors of the Indonesian people who grew and developed in a particular community, passed down continuously from generation to generation. Games and play activities are important elements in students' lives. By playing games, students can achieve pleasure. Most traditional games and sports are expressions of indigenous cultures and ways of life that contribute to a shared identity. The main objectives of traditional games for primary school students are: 1) Encourage students' creativity; 2) Improving students' social and emotional intelligence; 3) As a tool for learning values; 4) Sharpening students' motor and biomotor skills; 5) Contributing to health; 6) Optimizing students' cognitive abilities; 7) Provide happiness and joy. The purpose of this service activity is to provide knowledge to students about local culture through traditional games that are certainly interesting to play, where not only students, but also adults often enjoy traditional games. Since the tools used come from nature and are made from readily available materials, it is easier for users to obtain them. These traditional games encourage students to interact, and even the spectators of these games will feel the excitement and witness the game. The games include jumping rope, bekel and dakon. The activity stages in this activity include identification and preparation. Collaborating with the school, preparing modules and teaching materials, and preparing tools and materials for traditional game activities. Activity implementation included interactive presentation sessions on local culture and showing traditional game tools. Traditional games included role-playing by students and the team, which was then followed by the practice of playing in turns by students in small groups. Students are directed to practice and perform the assigned traditional games. Assessment and rethinking. Evaluate the speed, accuracy and thoroughness of the students while playing and reflect together to discuss the experience and new knowledge gained. Documentation and reporting. Record all activities and compile a report that covers the objectives. Most students understand the rules in playing jump rope, bekel ball, and dakon. Students are also able to practice the three traditional games well. They also like these three traditional games and will play these games when there is free time such as during recess. The team gave appreciation to the students by giving rewards to all students who had participated in this activity well. Introducing local culture through traditional games at SDN Sukorejo is a success in preserving traditional games and providing students with an understanding of local culture. This activity succeeded in increasing students' understanding and skills in playing traditional games, and was also successful in socializing to the school.